The Mental Companion Mode of Nursing Robots——A Study on Affective Computing-Based Companionship Strategies for Alzheimer’s Disease Patients - Chen, Tingting; Guan, Jiajing (Innovative Applications of AI, 2025)
This study aims to investigate the application of nursing robots based on affective computing theory in the companionship strategies for Alzheimer's Disease Patients. The research begins with a comprehensive literature review on the current development of nursing robots, clarifying the unique needs of Alzheimer's patients in terms of psychology, emotion, and social interaction. Based on the foundation of affective computing theory, a "mental companion" model is proposed, emphasizing the robot's ability to recognize and respond to human emotions during companionship to achieve more personalized care interactions. Through the design of Affective Interaction Technology, the study explores effective ways to integrate affective computing into nursing practice. Furthermore, specific companionship strategies are developed around this model, including intelligent response mechanisms and behavioral guidance for emotional states, to improve the quality of life for Alzheimer's patients. The effectiveness and feasibility of these companionship strategies in practical applications are verified through empirical research and case studies, demonstrating the potential value of nursing robots as emotional companions and providing theoretical support and practical recommendations for future related research and applications. This study holds significant academic and application value for enhancing the care quality and well-being of Alzheimer's patients and promoting the development of nursing robot technology.